Measurements for long-term care : a guidebook for nurses - Beaton, Sarah Reese (Sage Publications, 1998)
Measurements for Long-Term Care lists instruments alphabetically by name. Each entry includes the name of the tool's author (with address), a description of the tool, its psychometric properties, procedure for administration, sample items, information about scoring, sources for the tool, and references. The book also includes a chapter about how to update tool information and find new instruments, a list of abbreviations and acronyms, and indexes for instrument authors' names, nursing diagnoses, subjects (client disorders and problems), and instrument titles. Measurements for Long-Term Care will prove an excellent shelf and clinic reference for researchers, faculty, clinicians, and advanced-level students in long-term and chronic care, gerontologic nursing, and rehabilitation nursing.